PEMBERIAN MADU TERHADAP GRADE LUKA GANGREN PADA PASIEN DIABETES MELLITUS TIPE II POST OPERASI DEBRIDEMENT - Rahayu, Safitri; Andriati, Riris; Pratiwi, Rita Dwi; Pratama, Defi Anggara; Indah, Fenita Purnama Sari (Edu Masda Journal, 2024)
Symptoms of tingling, pain in the hands and feet and reduced sensitivity or numbness will be very dangerous for the sufferer because if the sufferer is injured in the leg or hand the sufferer will not feel pain. Wounds will become more difficult to heal and then become ulcers/ulcers and can also become gangrene. Objective: To know the effect of honey administration on the degree of gangrene wounds in patients with diabetes mellitus. Methods: The research method used is a quasi-experiment design method using one design pre-test and post-test approach that compares subjects before and after giving honey therapy. Results: obtained 0,005 in the present by comparing the p-value to the critical p value is 0.05. The results of the influence test show that the degree of gangrene wound after giving treatment using honey in the Anggrek-Sakura Room of RSU Bhakti Asih Ciledug Tangerang normal distribution of 0.441. Conclusion: there is an influence of the administration of honey therapy against the grade of the gangrenous wound in patients with diabetes mellitus type 2 post-operation debridement. Recommendation: From the results of this study, it is expected that educational institutions can improve and define various educational programs that can disseminate information about the administration of honey for grade gangrene wounds in patients with type 2 diabetes mellitus.AbstrakKondisi gejala kesemutan, nyeri pada tangan dan kaki serta berkurangnya sensitivitas atau mati rasa akan sangat berbahaya bagi penderita karena apabila penderita terluka dikaki atau tangan penderita tidak akan merasa sakit. Luka akan semakin sukar sembuh dan kemudian menjadi ulkus/borok dan bisa juga menjadi luka gangren. Tujuan: Mengetahui pengaruh pemberian madu terhadap grade luka gangren pada pasien diabetes mellitus. Metode: Metode penelitian yang digunakan adalah metode quansi eksperiment design dengan menggunakan pendekatan one design pre-test dan post-test yaitu membandingkan subjek sebelum dan sesudah diberikan terapi madu. Hasil: Diperoleh p value 0,005 di tunjukan dengan membandingkan nilai p terhadap nilai p kritis yaitu 0,05. Hasil uji pengaruh diketahui bahwa grade luka gangren sesudah diberikan perawatan terapi menggunakan madu di Ruang Anggrek-Sakura RSU Bhakti Asih Ciledug Tangerang berdistribusi normal sebanyak 0,441 Kesimpuan: Bahwa ada pengaruh pemberian terapi madu terhadap grade luka gangren pada pasien diabetes mellitus tipe 2 post operasi debridement. Saran: dari hasil penelitian ini diharapkan institusi Pendidikan dapat meningkatkan dan menentukan berbagai program pendidikan yang dapat menyebarluaskan informasi tentang pemberian madu terhadap grade luka gangren pada pasien diabetes mellitus tipe 2.